Breakup of rotating asymmetric quartic-quadratic trapped condensates - Brito, Leonardo; Andriati, Alex; Tomio, Lauro [UNESP]; Gammal, Arnaldo (Amer Physical Soc, 2020)
The threshold conditions for a rotating pancakelike asymmetric quartic-quadratic confined condensate to break in two localized fragments, as well as to produce a giant vortex at the center within the vortex-pattern distributions, are investigated within the Thomas-Fermi (TF) approximation and full-numerical solution of the corresponding Gross-Pitaevskii (GP) formalism. By comparing the TF predictions with the GP solutions, in our investigation with two different quartic-quadratic trap geometries, of particular relevance is to observe that the TF approach is not only very useful to display the averaged density distribution, but also quite realistic in establishing the critical rotational conditions for the breakup occurrence and possible giant-vortex formation. It provides almost exact results to define the contour of the condensate distribution, even for high rotating systems, after the system split into two (still confined) clouds. The applicability of the Feynman rule to the vortex distribution (full-numerical GP solutions) is also being confirmed for these nonhomogeneous asymmetric trap configurations. This study is expected to be relevant for manipulating the rotation and trap parameters in addition to Feshbach resonance techniques. It can also be helpful to define initial conditions for any further studies on the dynamical evolution of vortex pattern distributions.